2 '- 1-(4-chloro-2-hydroxyphenyl)ethylidene -benzenesulfonohydrazide - Ali, Hapipah Mohd; Ng, S.W.; Jefrey, B.W.; Laila, M. (International Union of Crystallography, 2007)
Two molecules of the title compound, C14H13ClN2O3S, are linked by two N-H center dot center dot center dot O-sulfonyl hydrogen bonds about a center of inversion to furnish a hydrogen-bonded dimer.